Multiple-Condensates effects in novel superconducting materials - CAVALCANTI, Paulo José Fonseca (2020)
Coupled condensates with diverse coherence length scales interfere (interact) constructively or destructively, which leads to unconventional non-single-condensate physics. In the Thesis we investigate two phenomena governed by multiple condensates: the dependence of the superconducting magnetic response on the number of contributing bands and the multiband mechanism of screening the superconducting fluctuations. The first problem is related to the tacit assumption that multiband superconductors are essentially the same as multigap superconductors. More precisely, it is usually assumed that the number of excitation gaps in the energy spectrum determines the number of contributing bands in a relevant superconducting model capable to capture the essential physics. Here we demonstrate that contrary to this widely accepted perception, the superconducting magnetic properties are sensitive to the number of contributing bands even for degenerate excitation gaps. In particular, we find that the crossover between super conductivity types I and II and the related intertype physics are affected by difference between characteristic lengths of multiple contributing condensates. Coupled condensates interfere (interact), which results in non-single-condensate physics regardless of a particular structure of the excitation spectrum. The related formalism is based on the -expansion of the microscopic equations, with = 1− /c the proximity to the critical temperature, and goes to one order beyond the standard Ginzburg-Landau (GL) approach to capture a finite intertype crossover domain in the phase diagram of the superconducting magnetic response. Previously this extended GL formalism has been constructed for single- and two-band systems. In this work we generalize that formalism to the case of an arbitrary number of contributing bands. The second problem is focused on the superconducting fluctuations in systems with multiple coupled condensates. It is well known that superconductivity in quasi-one-dimensional (Q1D) materials is hindered by large fluctuations of the order parameter. They reduce the critical temperature and can even destroy the superconductivity altogether. Here we demonstrate that the situation changes dramatically when a Q1D pair condensate is coupled to a higher-dimensional stable one, as in recently discovered multiband superconductors with Q1D band(s). The fluctuations are suppressed even by vanishingly small pair-exchange coupling between different band condensates and the superconductor is well described by the mean field theory. In this case the low-dimensionality effects enhance the coherence of the system instead of suppressing it. As a result, the temperature of the multiband Q1D superconductor can increase by orders of magnitude when the system is tuned to the Lifshitz transition with the Fermi level close to the edge of the Q1D band.